2019
DOI: 10.1085/jgp.201912351
|View full text |Cite
|
Sign up to set email alerts
|

Glucose stimulates somatostatin secretion in pancreatic δ-cells by cAMP-dependent intracellular Ca2+ release

Abstract: Somatostatin secretion from pancreatic islet δ-cells is stimulated by elevated glucose levels, but the underlying mechanisms have only partially been elucidated. Here we show that glucose-induced somatostatin secretion (GISS) involves both membrane potential-dependent and -independent pathways. Although glucose-induced electrical activity triggers somatostatin release, the sugar also stimulates GISS via a cAMP-dependent stimulation of CICR and exocytosis of somatostatin. The latter effect is more quantitativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 66 publications
1
28
0
1
Order By: Relevance
“…If cAMP promotes CICR, one would expect to see [Ca 2+ ] i spikes that are unrelated to membrane potential. This was indeed what Denwood et al (2019) observed. Increases in cAMP sometimes induced “spontaneous” [Ca 2+ ] i spikes even when the membrane potential was clamped at −70 mV.…”
supporting
confidence: 86%
See 4 more Smart Citations
“…If cAMP promotes CICR, one would expect to see [Ca 2+ ] i spikes that are unrelated to membrane potential. This was indeed what Denwood et al (2019) observed. Increases in cAMP sometimes induced “spontaneous” [Ca 2+ ] i spikes even when the membrane potential was clamped at −70 mV.…”
supporting
confidence: 86%
“…CICR is enhanced by glucose but it has been unclear how the sugar acts in this process. The present study ( Denwood et al, 2019 ) pinpoints the intracellular messenger cAMP as the amplifying factor in glucose-stimulated somatostatin secretion.…”
mentioning
confidence: 64%
See 3 more Smart Citations